Treatment of Chronic Hepatitis C Virus Infection in Dialysis Patients: An Update. (2nd September 2010) - Weclawiak, Hugo; Kamar, Nassim; Ould-Mohamed, Abdellatif; Cardeau-Desangles, Isabelle; Izopet, Jacques; Rostaing, Lionel
Abstract : Hepatitis C virus (HCV) infection is a blood-borne infection and its prevalence used to be elevated in hemodialysis (HD) patients. Its main mode of contamination relies on nosocomial transmission. HCV infection is frequently associated in HD patients with normal liver enzymes whereas liver histology can display some degree of HCV-related lesions. The assessment of HCV-related lesions, even in HD dialysis patients, can be done via noninvasive tests. After kidney transplantation, HCV-related lesions can worsen; however, in this setting antiviral treatment harbors the risk of acute rejection. Therefore, it is recommended to implement antiviral treatment while the patient is receiving dialysis therapy. In this setting, the rate of viral clearance is usually high. In case of sustained virological response, no relapse occurs after kidney transplantation, despite heavy immunosuppression.